REKOMENDACJE DLA STRATEGII FIRM POLSKICH WOBEC EKSPANSJI INWESTORÓW ZAGRANICZNYCH - Gorynia, Marian; Jankowska, Barbara (Wydział Prawa i Administracji UAM, 2005)
The paper is an attempt to define some practical recommendations which Polish companies could adopt in view of growing competition resulting from foreign investments in Poland. The proposed strategies are based on the results of an empirical research which was financed by the State Committee for Scientific Research in Poland. The project examined the strategies that had already been used by Polish companies in respect on the foreign competitors and foreign capital entering the Polish market in a variety of legal forms, with a special focus on direct investments. Selected actual cases of market competition described in professional publications are also discussed. The opinions presented in the paper have been grounded on those economic theories and doctrines which seem to gaining popularity and often serve as the foundation of the strategies, which are being adopted by many enterprises. The conclusion offered is rather optimistic, as Polish enterprises as seen to be confronting foreign competitors from a position that is not, ex definitione, a lost one. However, successful strategies should be based on carefully developed sources of a competitive advantage.
RECOMMENDATIONS OF A STRATEGY FOR POLISH COMPANIES FACING AN EXPANSION FOREIGN INVESTMENTS